Design and Development of Scuba Diving Learning Application Mobile-Based - Henry Valentino Florensius Kainde; Salaki Reynaldo Joshua; Yuri Vanli Akay (Jurnal Teknik Elektro dan Komputer, 2022)
Information technology has now become a very important need for all person. The development of Information Technology is very fast in various community needs. Information technology is very helpful in various fields, one of which is being a media learning. Diving is currently one of the most popular sports. The underwater beauty of Indonesia makes its own magnet for people to enjoy it personally direct. Diving knowledge must be mastered by novice divers to avoid underwater risk. Diving instructors or trainers can provide basic prior knowledge divers can practice diving underwater. Beginner divers must learn and know how to dive well and must know the risks in diving. The purpose of this research is to develop a mobile software based on android to be able to provide digital learning and information to students beginner divers in learning the right thing about the sport of diving. In this research will carried out in a number of stages, namely Literature Study, Data Collection, System Design and Data Modeling, System Development and Data Processing, Testing and Evaluation, Reporting and Publication.